2016
DOI: 10.7753/ijcatr0511.1002
|View full text |Cite
|
Sign up to set email alerts
|

Activity Context Modeling in Context-Aware Environment

Abstract: Abstract:The explosion of mobile devices has fuelled the advancement of pervasive computing to provide personal assistance in this information-driven world. Pervasive computing takes advantage of context-aware computing to track, use and adapt to contextual information. The context that has attracted the attention of many researchers is the activity context. There are six major techniques that are used to model activity context. These techniques are key-value, logic-based, ontology-based, object-oriented, mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The completed questionnaire was normalized by using zeros and ones which resulted in 32 unique records as depicted in Table I. A value of one (1) indicates that a category of activity is available for ranking and selection, otherwise, the value is zero (0). Table I shows the input and output values.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The completed questionnaire was normalized by using zeros and ones which resulted in 32 unique records as depicted in Table I. A value of one (1) indicates that a category of activity is available for ranking and selection, otherwise, the value is zero (0). Table I shows the input and output values.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…The ability to design an intelligent reasoning engine for context-aware mobile applications has prompted many researchers to devise various mechanisms. Previous mechanisms included if-then rules, key-value, logic-based and ontology-based models [1]. Following the use of ontology-based models complemented with other technologies in acquiring activity context, Dey [2], Naeem et al [3] and Sherif and Alesheikh [4] suggested the need to use machine learning approach in designing context-aware applications.…”
Section: Introductionmentioning
confidence: 99%